Mass Clonal Multiplication of Casuarina equisetifolia by Rooting Cladode Segments - Pal, Mohinder; Kumar, Adarsh; Bakshi, Meena; Bhandari, H. C. S. (Indian Forester, 1994)
A new technique of macropropagation by rooting small segments of cladodes for rapid mass multiplication of clonal material of Casuarina equisetifolia L. is described. Even as small as 2.0 cm long cladode segments can be rotted if maintained under high humidity. The size of cladode segments, position of the cladode on the shoot, auxin treatment, season of taking and planting the segment and age and genotype of the mother plant were found to affect the rooting ability of the cladode segments. The significance of this technique for the mass multiplication of the superior clonal material of C. equisetifolia is discussed.